2012
DOI: 10.1111/j.1464-5491.2012.03628.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cystatin C‐ and creatinine‐based estimation of glomerular filtration rate according to glycaemic status in Type 2 diabetes

Abstract: Performance of cystatin C-eGFR was superior to creatinine-based GFR in patients with Type 2 diabetes with HbA(1c) >95 mmol/mol (10.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Hence, the authors recommended incorporating cystatin C when testing for renal function [46]. Similar results have also been reported by other study groups who propose the use of cystatin C based formulae as it has been shown to be comparable [47] or superior [48] to creatinine-based estimations of GFR in patients with type 2 diabetes.…”
Section: Cystatin C In Type 2 Diabetes Mellitussupporting
confidence: 80%
“…Hence, the authors recommended incorporating cystatin C when testing for renal function [46]. Similar results have also been reported by other study groups who propose the use of cystatin C based formulae as it has been shown to be comparable [47] or superior [48] to creatinine-based estimations of GFR in patients with type 2 diabetes.…”
Section: Cystatin C In Type 2 Diabetes Mellitussupporting
confidence: 80%
“…This greater bias in people with diabetes was especially evident when eGFR was > 90 ml min À1 1.73 m À2 [4]. Other studies have also shown that the CKD-EPI formula is less accurate in people with diabetes compared with healthy individuals [7] and that the CKD-EPI, MDRD and Cockcroft-Gault formulas underestimate GFR in patients with diabetes [8,9]. It has even been suggested that the CKD-EPI formula may not offer any particular advantages over the MDRD formula in people with diabetes [10].…”
Section: Introductionmentioning
confidence: 98%
“…In the pooled CKD-EPI study data set, an estimated GFR (eGFR) calculated from the CKD-EPI formula underestimated measured GFR in people with diabetes by 4.6 ml min À1 1.73 m À2 on average compared with only 1.3 ml min À1 1.73 m À2 in those without diabetes. Other studies have also shown that the CKD-EPI formula is less accurate in people with diabetes compared with healthy individuals [7] and that the CKD-EPI, MDRD and Cockcroft-Gault formulas underestimate GFR in patients with diabetes [8,9]. Other studies have also shown that the CKD-EPI formula is less accurate in people with diabetes compared with healthy individuals [7] and that the CKD-EPI, MDRD and Cockcroft-Gault formulas underestimate GFR in patients with diabetes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The MDRD-eGFR underestimated isotopic GFR in the group with HbA1c > 95 mmol⁄ mol; however, there was no statistically significant difference between eGFRcys and isotopic GFR. Although the performance of eGFRcys in this study was not superior to MDRD-eGFR in the patient groups with HbA1c < 95 mmol⁄ mol, there is an improved performance of eGFRcys in the groups with HbA1c > 95 mmol⁄ mol [57]. Cystatin C-based eGFR was also found to be correlating well with glycemic status (expressed by the fasting glucose and the HbA1c) in type 2 diabetes in Mathew et al study, indicating that it is the marker of choice for the detection of renal involvement in patients with type 2 diabetes [54].…”
Section: Cystatin C-versus Creatinine-based Estimating Equationsmentioning
confidence: 85%